GROWTH RESPONSE of Acartia sp.TO THE APPLICATION OF EGG YOLKS, PELLETS AND YEAST AS A SOURCE OF NUTRITION - Muliani, Muliani; Fahrezza, Fahrezza; Rusydi, Rachmawati; Ayuzar, Eva; Salamah, Salamah (Journal of Fish Nutrition, 2021)
Acartia sp is a zooplankton that has the potential to be developed and used as natural feed for marine fish larvae. The problem in cultivation is that the right feed is needed as a support for the growth of Acartia sp so that maximum production and feed needs from larvae are fulfilled. This study aims to find out the growth response of Acartia sp to the application of egg yolks, pellets and yeast as a source of nutrition. Research parameters include abundance levels, population peaks, growth rates and water quality on Acartia sp maintenance. The research method is an experimental laboratory with 4 (four) treatment levels and 3 (three) repeats. The treatment standards are A: Pellets, B:Egg yolks, C: Yeast (yeast), and D: Nannochloropsis sp (control). The research phase consists of preparation of Acartia sp feed (egg yolk, pellet, yeast, and Nannochloropsis sp), feeding, and maintenance of Acartia sp. The results showed that acculturation of Acartia sp with feed differences affected daily abundance, population peak, and growth rate of Acartia sp with the best treatment indicated by Nannocloropsis sp (control). The peak population of Acartia sp reached 633.33 ind / L, the growth rate of Acartia sp reached 106.6 ind / day. However, the provision of pellets becomes an alternative to Acartia sp feed that has the potential to support its growth. The value of water quality parameters during the study is still optimal, namely temperature 25-27 Â°C, salinity 33-35 ppt, pH 7.1-7.9, DO 4.9-6.6 mg / L, and ammonia 0.087-0.284 ppm. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;"><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">